2011
DOI: 10.1186/1472-6963-11-229
|View full text |Cite
|
Sign up to set email alerts
|

Health facility committees and facility management - exploring the nature and depth of their roles in Coast Province, Kenya

Abstract: BackgroundCommunity participation has been emphasized internationally as a way of enhancing accountability, as well as a means to enhance health goals in terms of coverage, access and effective utilization. In rural health facilities in Kenya, initiatives to increase community accountability have focused on Health Facility Committees (HFCs). In Coast Province the role of HFCs has been expanded with the introduction of direct funding of rural facilities. We explored the nature and depth of managerial engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(113 citation statements)
references
References 12 publications
7
105
1
Order By: Relevance
“…They worked in collaboration with community health workers and facility health workers to educate other community members in a village assembly on certain topical health issues, including the importance of child immunisation against various diseases. A study of HFCs and facility management in the Coast province of Kenya reported similar findings, in which facility committees organised health education talks at the facility level (Goodman, Opwora, Kabare, & Molyneux, 2011).…”
Section: Discussionmentioning
confidence: 76%
“…They worked in collaboration with community health workers and facility health workers to educate other community members in a village assembly on certain topical health issues, including the importance of child immunisation against various diseases. A study of HFCs and facility management in the Coast province of Kenya reported similar findings, in which facility committees organised health education talks at the facility level (Goodman, Opwora, Kabare, & Molyneux, 2011).…”
Section: Discussionmentioning
confidence: 76%
“…In Kenya, the lack of clarity on roles around budgetary control and oversight had negative implications for the relationship between heath committees and health facility workers (Goodman et al, 2011). Community based monitoring of health facilities and health services by HCs can at times create tense relationships between committee members and healthcare workers (Shukla et al, 2011;Singh et al, 2010).…”
Section: Provider Lack Of Awareness About Hcsmentioning
confidence: 97%
“…In Kenya, reforms including direct facility financing (DFF) increased the relevance of HCs (Goodman et al, 2011). Many interviewees felt that DFF widened the scope of HC activities because HCs could plan and implement activities with the additional finances, which increased their participation and developed their sense of facility ownership.…”
Section: Managerial Supportmentioning
confidence: 99%
See 2 more Smart Citations